THE IMPACT OF COVID 19 PANDEMIC ON THE INSTRUCTIVE-EDUCATIONAL PROCESS IN KINDERGARTEN - ADELA-SIMINA CÂMPAN; MUȘATA BOCOȘ (Studia Universitatis Babes-Bolyai, 2021)
ABSTRACT. We are all going through a difficult period, called into question by so many questions: the COVID 19 pandemic. Without a doubt, this pandemic has had and still has many implications both in the personal life of each of us and in our professional life. In addition to the fact that this virus affects our health, professional life has also been put to the test. The education system was not bypassed by challenges, therefore this period proved to be extremely demanding, with many implications on the instructive-educational activity. Preschool education has not been exempted from the impact of the changes that have occurred as a result of the outbreak of the pandemic. Teachers in the preschool education system have faced many difficulties in terms of teaching in the group. The instructive-educational process suffered in the context of the pandemic, being many variables to consider: the age peculiarities of preschoolers, the ways in which the teaching activities can be carried out through the platforms, the quality of the educational act through them, the lack of training of the teachers in this respect, the availability of parents to be able to supervise the preschooler during the synchronous online activities, etc. The present study presents the results of the application of a questionnaire addressed to teachers in preschool education, on the territory of Romania, which highlights the implications of the pandemic on the instructive-educational process in kindergarten.